Identification and Characterization of LEA Genes in Ash Tree (Fraxinus excelsior) Genome - UĞURLU BAYARSLAN, Aslı (Kastamonu University, 2019)
Aim of study: LEA proteins have a critical role in the abiotic stress response of plants. Ash belongs to the olive family and its genome sequence is complete. The LEA genes has not been extensively analyzed, although there are annotations in the ash genome. Therefore, it was aimed to perform genome-wide analysis of LEA genes in ash genome using bioinformatic tools in this study. Materials and methods: Ash and LEA protein sequences were obtained from the Ash Tree Genome and LEAP database respectively. Homologous LEA peptides in ash were found using CLC Genomic Workbench 11. Properties of ash LEA proteins were determined with Expasy PROTPARAM. MEGA7 was used to construct the phylogenetic tree. Functional analysis of ash LEA proteins was carried out via Blast2GO. miRNAs targeting transcripts of ash LEA proteins were detected with psRNATarget. The three-dimensional structures of ash LEA proteins were predicted using PHYRE2. Main result: 118 LEA genes (FexLEA) were identified in ash genome. FexLEA were divided into 5 distinct clusters according to phylogenetic analysis. The major molecular function of FexLEA was found as the binding activity. miR838 was the most common miRNA targeting FexLEA transcripts. Highlights: This study will provide the basis for further functional analysis of LEA proteins in ash.
Keywords: Dişbudak; LEA; Genom Analizi; Ash; LEA; Genome Analysis